Painted woman [videorecording (DVD)]. - Dawson, Stef; Dallas, Matt, 1982-; Craighead, Robert (Echo Bridge Home Entertainment, 2018)
A young woman looks to two men for salvation from her abusive marriage; a charming assassin and a wayward horse trainer. Which will help her escape, or can she save herself?